A Phase II Trial of Abiraterone With Dutasteride for Second‐Generation Antiandrogen‐ and Chemotherapy‐Naïve Patients With Castration‐Resistant Prostate Cancer. (17th January 2023) - Shiota, Masaki; Inoue, Ryo; Tashiro, Kojiro; Kobayashi, Keita; Horiyama, Shizuyo; Kanji, Hiromi; Eto, Masatoshi; Egawa, Shin; Haginaka, Jun; Matsuyama, Hideyasu
Abstract: The development of a novel therapy to overcome primary and acquired resistance to abiraterone is an unmet need. This study aimed to evaluate the efficacy and safety of adding 5α‐reductase inhibitor dutasteride to abiraterone, explore proof of concept, and identify candidates suitable for combination therapy. This phase II, single‐arm, and open‐label study enrolled second‐generation antiandrogen‐ and chemotherapy‐naïve patients with castration‐resistant prostate cancer. Patients received abiraterone and prednisolone for 4 weeks, followed by adding dutasteride. The primary end point was a 50% prostate‐specific antigen response rate. Serum concentrations of abiraterone and its metabolites as well as HSD3B1 and SRD5A2 genotypes were measured. The association between drug metabolism and genotypes and their impact on the efficacy of combination therapy were assessed. Among 21 patients, 18 (85.7%) achieved ≥50% PSA reduction. Median time to treatment failure was not reached during the median follow‐up of 15.4 months. No patients experienced grade ≥3 adverse events. Although dutasteride reduced serum 3‐keto‐5α‐abiraterone concentrations, higher serum 3‐keto‐5α‐abiraterone concentrations on combination therapy were associated with a shorter time to treatment failure. HSD3B1 and SRD5A2 genotypes were associated with serum Δ4‐abiraterone and 3‐keto‐5α‐abiraterone concentrations before adding dutasteride, respectively. Time to treatment failure was longer in patients with homozygous wild‐type HSD3B1, but comparable between those with the SRD5A2 genotype. The promising outcomes of this study warrant further investigation of combination therapy in a randomized trial. Stratification by HSD3B1 and SRD5A2 genetic profiles might identify patients suitable for combination therapy.